Assembling the pieces of macromolecular complexes: Hybrid structural biology approaches. Issue 16 (21st April 2015) - Politis, Argyris; Borysik, Antoni J.; Barran, Perdita; Cooper, Helen; Eyers, Claire
<x xml:space="preserve">Abstract</x> Hybrid approaches in structural biology have gained considerable interest for uncovering the molecular architectures of large and transient biological systems. In particular, MS‐based methods and structural electron microscopy can complement conventional tools, such as X‐ray crystallography and NMR spectroscopy. However, bringing together the data derived from diverse sources requires sophisticated methods that can efficiently deal with intrinsic ambiguities and heterogeneities of the vast amount of data available. Here, we highlight hybrid approaches for studying dynamic assemblies, such as transient soluble and integral membrane protein complexes. In this review, we emphasize the integration of the wide range of emerging MS‐based methods, such as ion mobility, native MS, hydrogen–deuterium exchange MS and chemical cross‐linking MS, with data acquired from cryo electron microscopy and X‐ray crystallography and further provide a future outlook of hybrid structural biology approaches.